Can information confusion caused by the financing model of new economy companies be eliminated? - Xuejing Xie; Weiguo Zhang (China Journal of Accounting Research, 2020)
New economy companies often use convertible and redeemable preferred shares with equity and debt characteristics as financing tools to reduce risk during their early stages of growth. According to relevant accounting standards, such preferred shares should be classified as financial liabilities and measured at fair value, with changes in fair value recognized in profit or loss. This can lead to confusing financial information: the better a company's development prospects, the higher its redemption or conversion price and loss, which can result in a large negative net asset value. A successful initial public offering, however, could offset large losses and negative net asset value. Following the development of accounting standards, this article thoroughly analyzes various proposals to modify relevant accounting standards and eliminate confusing information. This article also proposes possible problems and solutions as a reference for accounting standard setters and the various stakeholders in new economy companies.
Keywords: 650; New economy companies; Convertible and redeemable preferred shares; Hybrid instruments; Accounting standards